2010
DOI: 10.4149/neo_2010_03_241
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic stratification using F-18 FDG PET/CT in patients with advanced stage (Stage III and IV) non-small cell lung cancer

et al.

Abstract: 2, 12.09; p=0.0005). In conclusion, using the visual and quantitative analyses of F-18 FDG PET/CT, the responder to chemotherapy in advanced stage NSCLC patients had a better prognosis. Moreover, the potent predictor of prognosis in advanced stage NSCLC patients was %ΔSUV max .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 23 publications
1
7
0
Order By: Relevance
“…The prognostic value of 18 F-FDG PET is well known and has been established in other systemic treatments of breast cancer patients (31)(32)(33). The results of the present study indicate that response to 18 F-FDG PET based on SUV max significantly predicts survival in our patient population.…”
Section: Discussionsupporting
confidence: 64%
“…The prognostic value of 18 F-FDG PET is well known and has been established in other systemic treatments of breast cancer patients (31)(32)(33). The results of the present study indicate that response to 18 F-FDG PET based on SUV max significantly predicts survival in our patient population.…”
Section: Discussionsupporting
confidence: 64%
“…The prognostic value of maximum SUV (SUVmax) at diagnosis has been evaluated in solid tumors, and these studies suggest that high SUVmax is associated with poor prognosis in esophageal cancer, head and neck cancer, and non-small cell lung cancer [8][9][10][11][12]. In addition, a small study of gastric lymphoma suggested a potential prognostic value of SUVmax on pretreatment FDG-PET [13].…”
Section: Introductionmentioning
confidence: 98%
“…The parameter used in this study for risk-stratification was a decrease in total lesion glycolysis (TLG) with a cut-off value of <50% [35]. Also, Kim et al emphasized the role of 18 F-FDG-PET/CT for prognostic stratification in 19 patients with advanced NSCLC (stage III and IV) using DeltaSUV (max) to retrospectively identify non-responders to chemotherapy [36]. The strong correlation between histological regression grading and overall survival was shown by the German Lung Cancer Cooperative Group (GLCCG), proving that patients showing regression grading IIb or III had significantly better progression free survival and overall survival [37].…”
Section: Discussionmentioning
confidence: 99%